Access to the talar dome through the posteromedial approach: an anatomical study - Farias Molina, Wellington; Galizia Heitzmann, Lourenço; Bottino Martins, Guilherme; Martins Pimenta, Luiz Sergio; Rasfasky Fiorot, Giezy; Almeida Fragalli, Ian (Journal of the Foot & Ankle, 2021)
Objective: To determine the posteromedial area of the talus that can be reached without malleolar osteotomy through the posteromedial approach. Methods: Fifteen human cadaveric ankles were dissected in standard fashion to expose the posteromedial talar dome. Seven of the approaches (46.7%) were done on the left ankle. We did not observe any significant difference between sides (chi-square test, p=0.715). Results: On average, 2.09 cm2 (range, 1.72-2.69) of the posteromedial talus dome or 15.27% (range, 12-20) of the total talus dome can be accessed without osteotomy. Conclusion: Osteochondral lesions within the area accessible through the posteromedial approach (mean 2 cm2), as seen on magnetic resonance imaging, may be treated without a medial malleolus osteotomy. Level of Evidence IV; Descriptive Study.